The prognostic value of splenic abnormalities in pretreatment 18F-FDG PET/CT in patients with complete response diffuse large B-cell lymphoma. Issue 5 (May 2023) - Wang, S.; Ju, H.; Bai, Y.; Wang, L.; Ding, Q.; Li, P.; Jiang, X.; Lin, X.
Abstract : AIM: To investigate whether spleen imaging characteristics of baseline 2-[ 18 F]-fluoro-2-deoxy-d- glucose ( 18 F-FDG) positron-emission tomography (PET)/computed tomography (CT) can help to predict the clinical outcome in complete response (CR) diffuse large B-cell lymphoma (DLBCL). MATERIALS AND METHODS: Three hundred and six patients with DLBCL were enrolled in the study and divided into recurrence and non-recurrence groups. The splenic abnormalities were compared using the chi-square test and quantitative indexes were compared using the t- test. The Cox proportional hazard regression model was used for univariate and multivariate analysis. Kaplan–Meier curves and log-rank tests were used to compare progression-free survival (PFS). Propensity score matching (PSM) was used to match patients with and without splenic abnormalities according to age, gender, and initial Ann Arbor stage at a 1:2 ratio (52:104); then the recurrence and PFS results were compared again. RESULTS: Age, international prognostic index (IPI), stage, splenomegaly, and focal splenic lesions were significantly different between the recurrence and non-recurrence groups. IPI, stage, baseline spleen mean standard uptake value (SUVmean)/liver SUVmean, splenomegaly, and focal lesions were selected by Cox single-factor analysis, and only focal lesions showed a statistical difference in terms of Cox multivariate analysis ( p= 0.022, hazard ratio [HR]: 2.843). After PSM, focal splenic lesions ( n= 20) were still statistically different ( p= 0.003) between the recurrence and non-recurrence groups, and this played an essential role in PFS forecasting ( p= 0.0004, HR: 3.767). CONCLUSION: Focal splenic lesions were identified as an independent risk factor for the prognosis of DLBCL. Pretreatment splenomegaly and focal splenic lesions appeared to be related to the relapse and PFS of DLBCL patients. Focal splenic lesions still showed meaningful predictive value even with propensity matching. Highlights: PET/CT imaging reveals its advantage in assessing splenic involvement. Splenomegaly, focal splenic lesions, and diffuse metabolism are studied separately. Focal splenic lesions are an independent risk factor for the prognosis of DLBCL.